Transmission damage and repair strategy of quantum signaling in fiber channel - Zhao-peng YAN; Min NIE; Guang YANG (Tongxin xuebao)
The error state ratio is introduced by calculating the ratio of the error qubits and total amount of qubits which have been received.The reason of the error state yielded was analyzed to establish a quantum signaling transmission damage model in fiber channel.A quantum state equilibrium strategy was presented by using the quantum repeater technology and all-fiber polarization control scheme.After analyzing the effect of this strategy on damage model,the loss and dispersion of the quantum state during the fiber transmission will be compensated.The simulation results showed that this equilibrium strategy is able to reduce the error state ratio,and increase the quantum signaling effective transmission distance with the error state ratio below the 3% threshold.